Otitis Media with Persistent Inflammation is a Common Cause of Sensorineural Hearing Loss - Fatima Usman, Mehreen Babar, Wajih Ud Din Shinwari, Sajid Rashid Nagra, Salman Aftab Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of the research was to determine the rate of sensorineural hearing loss that is associated with chronic otitis media. Study Design: A Descriptive Cross-sectional study Place and Duration: Frontier Medical College, Abbottabad, from June, 2021 to November, 2021. Methods: Total 87 patients of both genders had age 15-55 years were presented. All the included patients had chronic suppurative otitis media clinical symptoms. Patients were enrolled after getting informed written consent from the patients. Through the use of a pure tone audiogram, we were able to determine the mean threshold of voice frequencies for sick as well as normal contralateral ears. In sick ears, a mean of more than 25 dB was considered to represent a positive case of SNHL. SPSS 24.0 was used to analyze all data. Results: We found that 49 (56.9%) patients were males and 38 (43.1%) patients were females. 17 (19.5%) cases had age 15-25 years, 35 (40.2%) patients had age 26-35 years, 25 (28.7%) patients had age 36-45 years and 10 (11.5%) patients were aged between 46-55 years. Majority of the cases 51 (58.6%) were from urban areas. There were 50 (57.5%) cases had chronic otitis media duration <10 months and remaining had disease duration >10 months. Frequency of sensorineural hearing loss was found in 47 (54.02%) cases. Among 47 cases SNHL, 32 cases were aged between 31-55 years. Conclusion: We concluded in this study that patients with chronic otitis media had significantly higher number of sensorineural hearing loss, Among SBHL cases, patients were mostly aged between 31-55 years and disease duration was >10months. Keywords: Otitis Media, Sensorineural Hearing Loss,